PENGARUH BUDAYA KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SLUKE KABUPATEN REMBANG - novi kusumaningsih; Muhammad Tahwin (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2022)
Performance improvement for both individuals and groups becomes the center of attention in a effort to improve organizational performance both in quantity and quality. This research was conducted on employees of Sluke District, Rembang Regency. The methode used to determine the sample is non-probability sampling with saturated sampling technique, namely examining the entire population of 27 employess. Data was collected by means of questionnaires, interviews and observations. The data processing technique used SPSS 21, the fisrt step is so test the isntrument from the quetionnaire through validity test, reliability test, multiple regression test and determinations test. The result showed that: (1) work culture has a positive and significant effect on employee performance; (2) motivations has a positive and significant effect on employee performance; (3) work culture and motivation simultaneously have a positive and significant effect on employee performance.